Pengaruh Nilai Karakter Kejujuran Pada Anak Usia Dini 5-6 Tahun Melalui Kegiatan Market Day Di RA Nurul ‘Ain Jakarta Utara - Nurjanah, Siti; Yenita , Roza; Iskandar , Rhoma (CV. ITTC INDONESIA, 2024)
Siti Nurjanah, The Influence Of Honesty Values On Early Childhood Aged 5-6 Years Through Market Day Activities at RA Nurul Ain, North Jakarta (2024). Thesis. Jakarta : Faculty Of Educational Sciences, Early Sciences, Early Childhood Education Teacher Education, Panca Sakti Bekas,2024. This study aims to analyze the influence of honesty character values in early childhood through the market day activity at RA Nurul Ain. This research uses a qualitative approach with a descriptive method to obtain a deep understanding of the implementation of the market day activity in cultivating the honesty character in children aged 5-6 years. Data were collected through observation, interviews, and documentation during the activity. The results show that the market day activity effectively fosters the honesty character in early childhood. The children were trained to be honest in transactions and to understand the importance of honesty through direct learning in a supportive environment. This activity is supported by the active role of teachers who provide guidance and evaluation, as well as the use of habituation and socio-drama methods. The involvement of teachers in introducing the concept of honesty through stories and simulations before the activity proved to be crucial in helping the children understand the values being taught. The implications of this study suggest that the market day activity can be an effective tool in character education for early childhood. Therefore, it is recommended that other educational institutions consider adopting or adapting similar activities in their efforts to instill character values in their students.